Repair of common arterial trunk: palliation and delayed correction as a viable alternative strategy in selected patients - Cuomo, Michela; Purbojo, Ariawan; Blumauer, Robert; Schober, Martin; Wällisch, Wolfgang; Dittrich, Sven; Cesnjevar, Robert (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES Primary repair of common arterial trunk (CAT) is burdened by high mortality rates, especially in the presence of multiple risk factors. Timing, possible palliative methods, optimal management of associated cardiac lesions and handling of a poor preoperative state are still under discussion. METHODS We retrospectively analysed all patients who underwent surgery for CAT in our institution between 2008 and November 2020. We included 22 patients, 11 of whom received primary correction (PC) and 11 of whom underwent initial palliation by partial repair, leaving the ventricular septal defect open and connecting the right ventricle to the pulmonary arteries with a small valveless right ventricle-to-pulmonary artery conduit. A delayed correction (DC) was performed after 11.5 ± 3.6 months. RESULTS The overall operative mortality was 4.5%; 1 patient (affected by severe truncal valve stenosis and presenting in a poor state preoperatively) in the DC group died after palliation. The incidence of postoperative pulmonary hypertensive crisis was significantly higher in the PC group (P = 0.027). No patient from either group required postoperative extracorporeal support. Survival rates after 6 years differed slightly (PC group, 90%; DC group, 70%; log-rank = 0.270). CONCLUSIONS PC of CAT remains an optimal surgical approach for patients with an expected low mortality. However, our data support palliation and DC as a suitable alternative strategy, especially in the presence of significant risk factors like interrupted aortic arch, poor preoperative condition or complex surgical anatomy.
CRIS-Team WoS Importer:2022-05-13
Keywords: Common arterial trunk; Palliation; Sano-Shunt; Outcomes; Patient-tailored therapy; Congenital cardiac surgery